Basic therapeutic approaches to the management of hematology/oncology patients with new coronavirus infection (COVID-19) - E. N. Misyurina; E. A. Baryakh; N. F. Frolova; O. N. Kotenko; Z. Yu. Mutovina; S. S. Andreev; T. N. Tolstykh; K. V. Yatskov; E. A. Karimova; A. B. Makeshova; O. A. Rukavitsyn; A. V. Misyurin; et al. (Онкогематология, 2024)
In December 2019, cases of severe respiratory infection were reported in Wuhan, China. The disease was caused by a new, previously undescribed coronavirus, structurally similar to the then known SARS-CoV virus. The World Health Organization has named the new virus SARS-CoV-2 and the disease it causes COVID-19. The problem of COVID-19 is exacerbated by the rapid spread of the SARS-CoV-2 virus and the development of life-threatening complications, the main of which is pneumonia. Due to the severity of the condition, from 5 to 10 % of patients are treated in intensive care units.SARS-CoV-2 initially attacks the respiratory system and causes symptoms such as fever, vomiting, headache, dizziness, general weakness, and diarrhea. Then these symptoms intensify in different directions, and the disease can often lead to death.Initially, only a few methods of symptomatic treatment were available and clinical trials of drugs that had previously shown their effectiveness against infection with the MERS-CoV and SARS-CoV viruses began. Temporary recommendations have appeared suggesting the use of some drugs both in monotherapy and in combination.In patients with hematologic malignancies, the immune response to the SARS-CoV-2 coronavirus is significantly reduced, which explains the high mortality rate (up to 38 %) of these patients hospitalized for SARS-CoV-2 infection. Recently, antiviral drugs and monoclonal antibodies have become available for pre- or post-exposure prophylaxis, as well as for early treatment of COVID-19. These treatments should be offered to patients at high risk of severe COVID-19 and to those who have not responded to vaccination. However, as changes in the genetic structure of the virus accumulate, some treatments may lose their clinical effectiveness against new variants.The combination of hematological malignancies and new coronavirus infection causes a more severe course of COVID-19 compared to the population and high mortality. Factors for an unfavorable prognosis for new coronavirus infection in patients with hematological malignancies include age over 60 years, a high comorbidity index, diagnoses such as acute leukemia, especially acute myeloid leukemia and myelodysplastic syndrome, disease status (relapse, progression, as well as newly diagnosed acute leukemia), severe COVID-19, agranulocytosis (myelotoxic or tumor).